A distant, cis-acting enhancer drives induction of Arf by Tgfβ in the developing eye - Zheng, Yanbin (Dev Biol, 2013)
The Arf tumor suppressor represents one of several genes encoded at the Cdkn2a and Cdkn2b loci in the mouse. Beyond its role blunting the growth of incipient cancer cells, the Arf gene also plays an essential role in development: Its gene product, p19(Arf), is induced by Tgfβ2 in the developing eye to dampen proliferative signals from Pdgfrβ, which effect ultimately fosters the vascular remodeling required for normal vision in the mouse. Mechanisms underlying Arf induction by Tgfβ2 are not fully understood. Using the chr4(Δ70kb/Δ70kb) mouse, we now show that deletion of the coronary artery disease (CAD) risk interval lying upstream of the Cdkn2a/b locus represses developmentally-timed induction of Arf resulting in eye disease mimicking the persistent hyperplastic primary vitreous (PHPV) found in Arf-null mice and in children. Using mouse embryo fibroblasts, we demonstrate that Arf induction by Tgfβ is blocked in cis to the 70 kb deletion, but Arf induction by activated RAS and cell culture “shock” is not. Finally, we show that Arf induction by Tgfβ is derailed by preventing RNA polymerase II recruitment following Smad 2/3 binding to the promoter. These findings provide the first evidence that the CAD risk interval, located at a distance from Arf, acts as a cis enhancer of Tgfβ2-driven induction of Arf during development.